Pengaruh Sistem Informasi Akuntansi, Pengendalian Internal Dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Kasus pada Karyawan Bagian Keuangan di UMKM Batu Alam Area Sukoharjo) - Budi Santoso; Aris Eddy Sarwono; Dewi Saptantinah PA (CV. ITTC INDONESIA, 2024)
Human resources are the biggest asset in a company. Human resources are one of the sources that determine the success of a company. Therefore, a company is required to set policies well in order to survive. Human resources are planners and active actors in a company. Without human resources, a company will certainly not be able to survive. This research aims to analyze the Influence of Accounting Information Systems, Internal Control, and Organizational Culture on Employee Performance Case Study on Finance Employees at UMKM Batu Alam Sukoharjo Area. This research uses a qualitative descriptive method with a case study approach. The research sample was determined using the Purposive Sampling method. The data collection used is document analysis, questionnaires. The COSO reference is applied by the researcher as the main analysis instrument. The results of this study show that the accounting information system has no effect on employee performance at UMKM Batu Alam Sukoharjo Area. Internal control has no effect on employee performance at UMKM Batu Alam Sukoharjo Area. Organizational culture has a positive and significant effect on employee performance UMKM Batu Alam Sukoharjo area. Accounting information systems, internal controls, and organizational culture have a simultaneous and significant effect on employee performance variables UMKM Batu Alam Sukoharjo area.